Beheira Survey: Roman pottery from the Western Delta of Egypt : Surface pottery analysis – Kilns - Kenawi, Mohamed (Rei Cretariae Romanae Fautorum Acta, 2012)
The Beheira Survey project started at the end of 2007 and en-ded in October 2010. The survey has documented 66 archaeo-logical sites in six districts in the Western Delta of Egypt. Among the sites surveyed there are 25 settlements where we did not find any architectural surface remains. Thus, the dates of these sites are based on the surface pottery collection. The intention of the Beheira Survey at the beginning was to collect all surface materials. Later it was found that this would be impossible for some sites because of the huge quantity of pottery fragments and long halfa grass. In order to not apply two different methods to the same region, it was decided to create at each site a single 20 × 20 m square, to locate this square by GPS, and to collect all the surface materials in it, counting and drawing the diagnostic pottery fragments. The reason for choosing the 20 × 20 m size was to give the best view of the materials at each site. The 20 × 20 m square is large enough to give a clear view of the materials on the site and can be compared with the other 20 × 20 m squares at other sites. Each 20 × 20 m area was located on the map to prevent any future mistakes and to allow others to continue the survey or to start an excavation on a systematic basis. In addition, horizontal grids/lines were created on each site with a distance of 10 m between them in order to be able to note all materials and/or hidden structures. We walked along these grid lines and any important evidence was collected, such as coins or glass. It is mentioned in the database if such extra materials were collected or not.